IMMUNE STATUS OF ORAL CAVITY DURING ORTHOPEDIC TREATMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The tasks of orthopedic dental treatment include not only replacement of defects of teeth or alveolar processes with prostheses, but also prevention of recurrence of the disease. That's why for to the prosthesis healer tool as is viewed from him reasonable use healer and prevention measures to see possibility gives _ [3,7] Xar different of materials prepared each how prosthesis or orthopedic device , one from the side healer tool is another _ on the other hand , himself unwanted ( side ) effect as manifestation to do can _ [1,5,9]. Recently, there have been significant changes in world dental practice, which has led to the emergence of new methods of treatment of dental anomalies, and developments and research related to the use of non-removable orthopedic prostheses have become increasingly important [1, 2, 8]. To date, the factors of local immunity of the oral cavity, the nature of physiological and pathological processes that occur when using non-removable bridge prostheses have not been studied [3-5, 9].